2007
DOI: 10.1002/elps.200600674
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of high‐throughput genotyping of whole genome amplified DNA in SNP genotyping studies

Abstract: Whole genome amplification (wga) of DNA is being widely implemented in many laboratories to extend the life of samples only available in limited quantities for genetic analysis. We determined the reliability of wgaDNA genotypes in three sets of replicates from the same individuals: (i) 23 pairs of genomic DNA (gDNA), (ii) 43 pairs gDNA versus wgaDNA, and (iii) 29 pairs of independently amplified wgaDNA. Amplification was performed using multiple displacement amplification (MDA). Genotyping was successful for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Concerns have been voiced over the lack of involvement of a clinician or genetic counselor in such testing (7 ), the regulation of such tests (8,9 ), ethical and legal issues (10,11 ), the variance in and the validity of risk (2,12 ), and the reliability of the overall analytical process and the possibility of genotyping errors (13)(14)(15). Our study found a Ͼ99.6% concordance in SNP genotypes among 3 DTC services (23andMe, deCODEme, Navigenics) and a genomics-analysis service (Expression Analysis).…”
Section: Brief Communicationmentioning
confidence: 99%
“…Concerns have been voiced over the lack of involvement of a clinician or genetic counselor in such testing (7 ), the regulation of such tests (8,9 ), ethical and legal issues (10,11 ), the variance in and the validity of risk (2,12 ), and the reliability of the overall analytical process and the possibility of genotyping errors (13)(14)(15). Our study found a Ͼ99.6% concordance in SNP genotypes among 3 DTC services (23andMe, deCODEme, Navigenics) and a genomics-analysis service (Expression Analysis).…”
Section: Brief Communicationmentioning
confidence: 99%
“…The validity of wgaDNA for ordinary use has been well justified [7], [14] and wgaDNA has previously been tested on medium-throughput MassARRAY platform with iPLEX GOLD chemistry [17]. However, to our knowledge, this study is the first one that made use of the variable multiplexing ability of the same genotyping technology to study the relationship between genotyping performance and multiplexing level of the assays using wgaDNA, and to examine whether the storage of wgaDNA would reduce the genotyping efficiency.…”
Section: Discussionmentioning
confidence: 97%
“…It can generate products with average size >10 kb, and the relatively consistent product yield is less sensitive to the amount of starting material [7], [11]. Whole genome amplified DNA (wgaDNA) from MDA methods can be used in a variety of applications including high-throughput genotyping [7], [14], e.g., Affymetrix array [15] and Illumina BeadArray [16]. In addition, the starting DNA sample for WGA needs not to be fresh [17].…”
Section: Introductionmentioning
confidence: 99%
“…In present study, we constructed the first high-resolution genetic map of M. amblycephala using SNPs, which represent the most common type of genome DNA polymorphism and are amenable to high-throughput genotyping31. Finally, an integrated map consisting of 24 LGs, which corresponded to 5,676 effective loci, was constructed based on 14,648 SNPs.…”
Section: Discussionmentioning
confidence: 99%